P013 Role of IL-36RA mutations in Crohn's disease. (30th January 2023) - Hecker, J; Saurenbach, J; Letizia, M; Löscher, B S; Franke, A; Kühl, A A; Atreya, R; Koop, K; Neufert, C; Trajanoski, Z; Schütz, A; Siegmund, B; et al.
Abstract: Background: The interleukin 36 (IL-36) family consists of three agonists (IL-36α, IL-36β, IL-36γ), that activate the NF-κB pathway and lead to the production of pro-inflammatory cytokines and the natural antagonist (IL-36RA), which inhibits IL-36 signaling. While it is known that IL-36 signaling is important in the skin, it has been only recently reported that IL-36 might play an important role in maintaining gut homeostasis and in the development of fibrosis (Scheibe et al., 2019). Here, we aim to understand how IL-36RA mutations contribute to development and maintenance of intestinal inflammation in Crohn's disease. Methods: By whole-exome sequencing (WES) and subsequently targeted Sanger sequencing we identified a Crohn's disease (CD) patient with a heterozygous missense mutation in IL-36RA (p.Ser113Leu). To understand how the mutation affects immune cells composition and function, we characterized peripheral blood mononuclear cells (PBMCs) of the patient by mass cytometry and measured cytokine levels in the serum by ELISA. In an available WES dataset of 177 CD patients, 47 ulcerative colitis (UC) patients and 34 healthy donors (HD), we searched for additional patients with IL-36RA mutations. Finally, we overexpressed the identified IL-36RA mutations in HEK cells and produced mutated recombinant proteins to study the effect of the mutations on protein expression and function. Results: Our IL-36RA mutation-carrying patient presented with a severe course of Crohn's disease and consecutive of fibrosis, which was resistant to all commonly used treatment options. In the patient, we detected increased levels of IL-36RA, IL-18 and IL-23 in the serum and an increased frequency of TH17 cells in the blood. These findings could hint towards an over-activation of the IL-36 signaling pathway in the IL-36RA mutated patient. In the available WES data, we identified two more CD patients with IL-36RA mutations (p.Leu133Ile, p.Pro76Leu), indicating that IL-36RA mutations are enriched in CD patients. By overexpressing the three identified mutations in HEK cells, we could demonstrate that two mutations (p.Ser113Leu and p.Pro76Leu) lead to a reduced protein expression. Also, our current data shows that the p.Ser113Leu mutant has a reduced capacity to antagonize IL-36 stimulation. However, further testing is required for the two other IL-36RA mutants. Conclusion: Our data suggests that IL-36RA mutations are enriched in Crohn's disease patients and should be considered as a possible cause for therapy-refractory and fibrotic Crohn's disease.